2013
DOI: 10.1016/j.freeradbiomed.2013.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage and cellular defense mechanisms in sea urchin models of aging

Abstract: The free radical or oxidative stress theory of aging proposes that the accumulation of oxidative cellular damage is a major contributor to the aging process and a key determinant of species longevity. This study investigates the oxidative stress theory in a novel model for aging research, the sea urchin. Sea urchins present a unique model for the study of aging due to the existence of species with tremendously different natural life spans including some species with extraordinary longevity and negligible senes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…In fact, echinoderms do not show variations in metabolic functions and fertility over time, and no cases of cancer, immune and age-related diseases have been reported (Bodnar, 2009). In accordance, recent analysis of oxidative damage and proteomic studies in three sea urchin species with different lifespans revealed that the sea urchin is a promising tool for investigations of oxidative cell damage, senescence, and longevity (Bodnar, 2013;Du et al, 2013).…”
Section: Echinoderm Immune Cellsmentioning
confidence: 55%
“…In fact, echinoderms do not show variations in metabolic functions and fertility over time, and no cases of cancer, immune and age-related diseases have been reported (Bodnar, 2009). In accordance, recent analysis of oxidative damage and proteomic studies in three sea urchin species with different lifespans revealed that the sea urchin is a promising tool for investigations of oxidative cell damage, senescence, and longevity (Bodnar, 2013;Du et al, 2013).…”
Section: Echinoderm Immune Cellsmentioning
confidence: 55%
“…In a study that investigated the aging species of sea urchin short life and extraordinary longevity, found that levels were lower oxidative damage and antioxidant activity was higher in cells or tissues of long-lived species compared with short-lived species [7]. Consistent with the predictions of the oxidative stress theory of aging, the results suggest that the negligible senescence is accompanied by a decrease in cellular accumulation of oxidative damage with age, and maintenance of antioxidant status and the activities of enzymes of proteasome may be important mechanisms to mitigate the damage [7].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…There is substantial evidence showing that aging is associated with damage from free radicals represented by various reactive oxygen species (ROS) [7]- [9].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Oxidative stress in an organism is largely due to the accumulation of reactive oxygen species (ROS). By damaging nucleic acids, proteins, and other molecules, ROS decrease the lifespan of many organisms 106 , 107 . CR can promote lifespan by both lowering the production of ROS as well as promoting the function of antioxidants that can repair ROS-induced damage.…”
Section: Links Between Cr Oxidative Stress and Energy Metabolismmentioning
confidence: 99%